Vertical Distribution of Particulate Matter in a Near-highway Urban Area - MacNaughto, Piers Iain Ivo Octa (Tufts Archival Research Center, 2005)
This thesis describes research to better understand vertical profiles of particle number count and mass concentration of particles less than 2.5 ï¿½ï¿½m in diameter (PM2.5) near Interstate 93 in Boston, Massachusetts. These profiles can be used to help estimate particulate matter exposure to people who live or work several stories above ground-level. Although vertical profiles of particulate matter have been collected near major roadways in previous studies, none have been collected with as fine a spatial resolution and over as wide a range of meteorological conditions. The profiles were collected with a pulley system that lifted the instruments, leading to a continuous sampling of the vertical profiles. The vertical profiles are analyzed in conjunction with meteorological conditions, the source strength of the highway, and building density and height to obtain a qualitative assessment of each variable's effect on the magnitude and the slope of the particle profiles. The meteorological conditions considered in this thesis are wind direction and speed, temperature, and relative humidity on both a short and long timescale. The magnitude of the particle number count and PM2.5 is primarily dependent on the source strength and the diurnal temperature cycle. The slope of the particle number count profile depends on the vertical temperature profile, whereas PM2.5 remains constant with height. The profiles do not demonstrate a significant decline with height; therefore, exposure to particulate matter up to eight stories high should not be dismissed as an exposure pathway.